2020
DOI: 10.1007/s12687-020-00497-x
|View full text |Cite
|
Sign up to set email alerts
|

Communication about breast cancer genetic counseling with patients with limited health literacy or a migrant background: evaluation of a training program for healthcare professionals

Abstract: Access to breast cancer genetic counseling is suboptimal for patients with limited health literacy or a migrant background due to ineffective communication and lack of healthcare professionals’ recommendation. This study examines the effect of a blended training program (Erfo4all) for healthcare professionals on their awareness, knowledge, and self-efficacy towards communication about genetic counseling with patients with limited health literacy or a migrant background. In total, 59 breast surgeons and special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Our results highlight an unmet need in training NGHPs to discuss multigene panel testing in the context of HBOC, particularly to patients with poor health literacy. In the Netherlands, the use of plain language and the teach-back method improved the competencies of NGHPs in providing genetic counseling to breast cancer patients with poor health literacy (van der Giessen et al, 2021). These methods that empower shared decision-making are important elements in the mainstreaming pathway.…”
Section: Training Needs In Mainstreamingmentioning
confidence: 99%
“…Our results highlight an unmet need in training NGHPs to discuss multigene panel testing in the context of HBOC, particularly to patients with poor health literacy. In the Netherlands, the use of plain language and the teach-back method improved the competencies of NGHPs in providing genetic counseling to breast cancer patients with poor health literacy (van der Giessen et al, 2021). These methods that empower shared decision-making are important elements in the mainstreaming pathway.…”
Section: Training Needs In Mainstreamingmentioning
confidence: 99%
“…Health literacy training among healthcare professionals uses the techniques learned in the training, such as the teach‐back method and plain language, and felt more confident about health problems in the community (van der Giessen et al., 2021). Conduct training sessions and integrate knowledge and skills, especially when developing patient communication and assessment skills related to real environmental situations and conditions with patients or community members.…”
Section: Discussionmentioning
confidence: 99%
“…Riddle et al (2022) found that a course aimed at enhancing interpreters' preparedness for genomic results disclosure appointments was effective at improving interpreters' confidence during sessions. Alternatively, English-speaking GCs could consider trainings aimed at improving communication for limited health literacy patients, i.e., incorporating methods like the teach-back method and using simplified language in sessions, as there are several published studies on different models and interventions (Joseph et al, 2019;Riddle et al, 2021;van der Giessen et al, 2020;.…”
Section: Practice and Training Implicationsmentioning
confidence: 99%